Developing an instrument for measuring the spiritual attitude of high school students - Safa'at Ariful Hudha; Djemari Mardapi (REID (Research and Evaluation in Education), 2018)
Attitudinal competence is one the most fundamental concepts in social psychology. It is related to personal identity, moral, and ethics that gains popularity and becomes important in educational development. This research aims to develop an instrument to measure the spiritual attitude of high school students. The study was a research and development study consisting of four stages: (a) determining conceptual definition, (b) determining operational definition, (c) drawing indicators, and (d) constructing instrument. The quantitative data analysis was used to test the construct validity through Confirmatory Factor Analysis and the coefficient of construct reliability was used to estimate the instrument reliability. The results of the study show that: (1) the instrument to measure Moslems’ spiritual attitude is an inventory model of summated rating scale containing 35 items; (2) the construct validity was proven by the value of the standardized loading factor and considered as significant. The instrument reliability regarded as the construct reliability coefficient is 0.890 and the average variance extracted is 0.542; (3) the construct of the instrument produces a fit statistical evidence indicated by the Goodness of Fit Index = 0.91 (≥0.90), and Root Mean Square Error of Approximation = 0.032 (≤0.08). The results indicate that the construct of the measurement is suitable with the data. In addition, this research has confirmed that the spiritual attitude of high school students is constructed by seven aspects, namely resignation (tawakal), sincerity (ikhlas), thankfulness (syukur), patience (shabr), fear (khauf), hopefulness (raja’), and righteousness (takwa).